Six-month smell and taste recovery rates in coronavirus disease 2019 patients: a prospective psychophysical study. Issue 5 (23rd May 2021) - Petrocelli, M; Cutrupi, S; Salzano, G; Maglitto, F; Salzano, F A; Lechien, J R; Saussez, S; Boscolo-Rizzo, P; De Riu, G; Vaira, L A
Abstract: Background: The long-term recovery rate for coronavirus disease 2019 related chemosensory disturbances has not yet been clarified. Methods: Olfactory and gustatory functions were assessed with psychophysical tests in patients in the first seven days from coronavirus disease 2019 onset and one, two, three and six months after the first evaluation. Results: A total of 300 patients completed the study. The improvement in olfactory function was significant at the two-month follow up. At the end of the observation period, 27 per cent of the patients still experienced a persistent olfactory disturbance, including anosmia in 5 per cent of cases. As for taste, the improvement in the psychophysical scores was significant only between the baseline and the 30-day control. At the 6-month evaluation, 10 per cent of the patients presented with a persistent gustatory disturbance with an incidence of complete ageusia of 1 per cent. Conclusion: Six months after the onset of coronavirus disease 2019, about 6 per cent of patients still had a severe persistent olfactory or gustatory disturbance.